Recentering the Philosophical Foundations of Knowledge: The Case of Africa With a Special Focus on the Global Role of Teachers - Abdi, Ali A. (Alberta Journal of Educational Research, 2010)
The historical and actual marginalizations of African thought systems and knowledge constructions have been expansively responsible for the effectiveness of the dominant educational and governance systems imposed on Africa. The idea as well as the practice of these realities would conform to what Said (1993), Fanon (1967, 1968), and Memmi (1991) have called the cultural and psychosocial colonizations of both the physical and mental spaces of the conquered. The reality also speaks about the role of Europe’s most important thinkers such as Kant, Hobbes, and Voltaire, who all directly or indirectly paved the way for the projects of “de-philosophization” and “de-epistemologization” that still affect people’s lives. With the emergence of new cosmopolitanisms now creating highly multicultured societies in especially the so-called liberal democracies of the West, new contexts have also emerged of what one might counterintuitively call the “multiculturalization of knowledge marginalizations.” Thus there is an urgent need to aim for knowledge and learning multicentricities that both theoretically and pragmatically rewrite the learning trajectories of both the old colonized space and the new, still alienating multicultural classrooms. This article engages the historical and actual problematizations of the case and suggests some ideas for better possibilities that could enhance the schooling lives of current globally located learners.